Pore-scale simulation of miscible displacement in an inclined porous medium - Liu, Gaojie; Xu, Aoyu; Wang, Yongqiang; Lou, Qin (Frontiers in Energy Research, 2024)
This study investigates the displacement of two miscible fluids within an inclined porous medium at the pore scale, highlighting how the pore-scale microstructure, inclination angle, and viscosity ratio affect the interfacial instability between two fluids during displacement processes. An increase in inclination angle exacerbates the interfacial instability between fluids and the viscous fingering phenomenon. This viscous fingering expands the sweep range of displacing fluids, which improves the displacement efficiency. When θ>50 • , further increase in inclination angle will not cause significant changes in displacement efficiency. In addition, the viscosity ratio is a key factor affecting displacement efficiency. The larger the viscosity ratio, the greater the displacement efficiency. Furthermore, the critical viscosity ratio has been found, and any increase in the viscosity ratio above the critical value will not affect the displacement efficiency.